Analisis Standar Etika Pendidik Dalam Pendidikan Islam; Prespektif Hukum Islam - Fitriah, Salsa Billa; Fitriatin, Nur (JoIEM (Journal of Islamic Education Management), 2025)
Educators have a heavy duty and responsibility, namely to form a generation with morality and morality, however, at this time many teachers have not lived up to their role as educators and immoral cases committed by an educator have emerged. Therefore, this article aims to analyze the ethical standards of educators in the perspective of Islamic law as a reference and increase the awareness of educators and the application of ethical principles in educational practices in real life. This research uses a literature approach or library research method. The standard of educators in the perspective of Islamic law emphasizes the importance of forgiveness, inviting goodness, and being fair and gentle with students. Values related to social, worship, creed, and morals are also very important for educators, such as fear and piety to Allah. And for a good and Islamic educator must have the characteristics possessed by the Prophet Muhammad SAW, namely the traits of siddiq (honest), amanah (trustworthy), tabligh (conveying), and fathanah (intelligent)